Analysis of Preferences and Behavior of K-Pop Fans in Comsuming K-Pop Content on Youtube - Mahmudah Widya Damayanthi; Wahyunengsih (Sekolah Tinggi Agama Buddha Nalanda, 2023)
This journal analyzes the preferences and behavior of K-Pop fans in consuming K-Pop content on YouTube. Through an online survey of 50 active fan respondents, this study aims to understand preferences for music genres, favorite K-Pop artists, frequency of visits to K-Pop YouTube channels, preferred types of content, and interactions with content. The results show a wide variety of fan preferences and behaviors, with particular inclinations towards music genres, favorite artists and types of content. Fans actively engage through comments and shares. This study provides important insights to understand consumption of K-Pop content on YouTube.